2016
DOI: 10.1016/j.jad.2016.01.048
|View full text |Cite
|
Sign up to set email alerts
|

When perceptions defy reality: The relationships between depression and actual and perceived Facebook social support

Abstract: These results demonstrate that an asymmetry characterizes the relationship between depression and different types of Facebook social support and further identify perceptions of Facebook social support as a potential intervention target. (243 words; 250 max).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 47 publications
8
68
0
1
Order By: Relevance
“…In this light, individuals with higher levels of depression and anxiety may be more inclined to interpret or perceive SNS interaction as more negative regardless of the communication content exchanged between users. The potential for such a perceptual bias in interpreting SNS interactions has also been suggested in reference to social support perceptions and is further discussed below (see Park et al [93]).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In this light, individuals with higher levels of depression and anxiety may be more inclined to interpret or perceive SNS interaction as more negative regardless of the communication content exchanged between users. The potential for such a perceptual bias in interpreting SNS interactions has also been suggested in reference to social support perceptions and is further discussed below (see Park et al [93]).…”
Section: Resultsmentioning
confidence: 98%
“…SNS users with depression differ from users without depression in that they express negative affect more frequently, use more personal pronouns, and generally have lower frequencies of interaction with others in their SNS network [91,92]. Park et al [93] have shown that individuals with a diagnosis of MDD more frequently post negative sentiment than those who are not depressed, and Moreno and colleagues [85,94] demonstrated that depression could be identified in the language used in the Facebook posts of college students based on the Diagnostic and Statistical Manual of Mental Disorders (Fourth Edition) criteria for MDD.…”
Section: Resultsmentioning
confidence: 99%
“…At a broad level, the frequent expression of negative affect within social media status updates has been associated with higher levels of depression symptoms [2,3,5,[7][8][9][10]. Frequently expressing positive affect, on the other hand, tends to be associated with lower levels of depression and greater levels of well-being [8,11,12].…”
Section: Depression In Status Updates On Social Mediamentioning
confidence: 99%
“…Considering the frequent use of emotion language in status updates that relate to current experiences [13,14], for a large proportion of the population social media can provide unobtrusive access to time-sensitive and ecologically valid samples of expressed emotion [2,[41][42][43]. While observations of emotion variability and instability are yet to be applied to social media as a means of automatically screening for individuals at risk of depression, depression change has been demonstrated to be visible through changes in status update posting activity and content [2,4,10,44,45].…”
Section: Social Media and Emotion Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation